Organocatalytic Asymmetric Synthesis of Pentasubstituted Tetrahydrothiopyrans Bearing a Quaternary Centre through a Double Michael Reaction - Mondal, Buddhadeb; Pan, Subhas Chandra (Synlett, 2018)
An organocatalytic, asymmetric, double-Michael strategy has been developed employing trans-α-cyano-α,β-unsaturated ketones for the synthesis of pentasubstituted tetrahydrothiopyrans bearing a quaternary center. A proline-derived bifunctional thiourea was found to be the most effective catalyst for this reaction. With 10 mol% of catalyst, good yields and good to high diastereomeric ratios, as well as excellent enantioselectivities, were obtained with a variety of tetrahydrothiopyrans under mild reaction conditions.
Keywords: tetrahydrothiopyrans; Michael reaction; organocatalysis; enantioselectivity; quaternary centers